Acquisition versus greenfield: The impact of the mode of foreign bank entry on information and bank lending rates - Sophie Claeys; Christa Hainz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
Policy makers often decide to liberalize foreign bank entry but at the same time restrict the mode of entry. We study how different entry modes affect the interest rate for loans in a model in which domestic banks possess private information about their incumbent clients but foreign banks have better screening skills. Our model predicts that competition is stronger if market entry occurs through a greenfield investment and therefore domestic banks' interest rates are lower. We find empirical support for our results for a sample of banks from ten Eastern European countries for the period 1995-2003.
urn:nbn:de:bvb:19-epub-13369-2
Keywords: G21; D4; L31; 330; banking; foreign entry; mode of entry; interest rate; asymmetric information